UPAYA PERLINDUNGAN HUKUM TERHADAP INFORMASI MEDIS PASIEN SEBAGAI AKSES LAYANAN ARSIP - Adella Syafira Habsari (JOURNAL IURIS SCIENTIA, 2024)
Legal protection is the provision of protection or protection for human rights. Personal data protection is related to the concept of privacy which requires protection for its confidentiality. Archives in their various forms of media are a source of information and collective memory that can increase national awareness, emphasize the identity and identity of the Indonesian nation. It would be more dangerous if there were archives in the form of personal data which is a trace data of the patient's medical record which is very confidential, so there are several special regulations such as Law Number 29 of 2004 con- cerning Medical Practice which regulates that every Doctor and Dentist in Carrying out medical practice must create medical records and these medical records must be kept confidential by the Doctor or Dentist and the head of the health service facility. The medical record file belongs to the health service facility and its contents in the form of a summary of the medical record belong to the patient. The summary can be given, recorded or copied by the patient or person authorized to do so or with the written consent of the patient or their family who have the right to do so